2021
DOI: 10.21608/ejp.2021.90889.1041
|View full text |Cite
|
Sign up to set email alerts
|

Disease Incidence and Genetic Analysis of Adult Plant Resistance to Leaf Rust in Some Egyptian Wheat Cultivars

Abstract: This research has been carried out to study the disease incidence and genetic analysis of adult plant resistance to leaf rust in eight Egyptian wheat varieties, Misr1, Misr2, Misr3, Gemmeiza11, Gemmeiza12, Sids1, Shandweel-1 and Sakha94 crossed with Triticum spelta saharensis (T.s.s.) as a highly susceptible tester wheat variety at Bahtem Agricultural Research Station, Agr. Res. Center during 2018-2021 growing seasons. The nine wheat genotypes and F2 plants of eight crosses with T.s.s. were estimated to diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…This supporting the hypothesis of one another dominant gene rules the resistance to leaf rust disease in this cross. These results agree with EL-Orabey et al (2020) and Mabrouk et al (2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This supporting the hypothesis of one another dominant gene rules the resistance to leaf rust disease in this cross. These results agree with EL-Orabey et al (2020) and Mabrouk et al (2021).…”
Section: Discussionsupporting
confidence: 93%
“…These high estimates also suggest that selection for this feature may be achievable during the initial generations of segregation. Given how crucial dominant impacts are to the evolution of this trait, a delay would be more effective (Abd El-Latif and Boulot, 2000;Menshawy and Youssef, 2004;Da-Silva et al, 2012;Loladze et al, 2014;Hermas and El-Sawi, 2015;EL-Orabey et al, 2020 andMabrouk, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yield component losses were the least in this group compared to other groups with different adult plant resistance and susceptible 'S' reaction. Similar results were described by various workers (Hailu and Fininsa 2009;Herrera-Foessel et al 2006;Safavi 2015;Mabrouk et al 2021;Dinglasan et al 2022) as they reported that the resistant cultivars have the least losses in yield components under high disease pressure. Although, cultivars in this group have resistant reaction with no pustulation, however, they showed minimum losses under high disease pressure.…”
Section: Discussionsupporting
confidence: 90%
“…These findings generally conflict with those recorded by Abdelbacki et al [30], who discovered that the cultivars Gemmeiza-11, Sakha-94, Sakha-95, Giza-168, Giza-171, Sids-12, Sids-13, Misr-1, and Misr-2 were resistant to leaf rust during the 2011/2012 and 2012/2013 growing seasons or had only moderate resistance. Moreover, Mabrouk [31] demonstrated that during the growing seasons of 2013-2016, the Gemmeiza-9, Gemmeiza-10, and Gemmeiza-11 wheat cultivars had FRS% ranging from 23.33 to 50% in four locations. These findings could result from the existence of new races in Puccinia triticina populations that can disrupt the resistance genes in these cultivars [32].…”
Section: Discussionmentioning
confidence: 99%